ESG and firm value: The moderating role of firm-specific contexts in Indonesia - Harindahyani, Senny; Eriandani, Rizky; Vanessa, Ardelia (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose – This study aims to examine the impact of environmental, social, and governance (ESG) performance on firm market value, while incorporating firm-specific contexts such as downside risk and upside potential as moderating variables. Methods – A quantitative approach was employed, using data from firms listed on the Indonesia Stock Exchange during 2018–2022 that had ESG scores from S&P Global Ratings. A total of 176 firm years were selected and analyzed using moderated regression analysis. Findings - The results reveal a negative relationship between ESG performance and firm value. However, financial risk and environmental risk significantly mitigate the negative impact of ESG on firm value, while financial stability and sales growth do not moderate the relationship. These findings emphasize that investors in emerging markets perceive ESG differently than those in developed economies. Implications - This research provides theoretical implications by enriching the literature on investor responses to ESG in developing countries, and practical insights for managers and investors in using ESG as a risk management tool.. Originality - Unlike prior studies in developed markets that highlight ESG’s positive role, this study shows that Indonesian investors tend to view ESG negatively unless it serves as an effective risk-reduction mechanism, highlighting the importance of firm-specific contexts.